Extensive Inter-Domain Lateral Gene Transfer in the Evolution of the Human Commensal Methanosphaera stadtmanae - Lurie-Weinberger, Mor N.; Peeri, Michael; Tuller, Tamir; Gophna, Uri (Frontiers in Genetics, 2012)
Methanosphaera stadtmanae is a commensal methanogenic archaeon found in the human gut. As most of its niche-neighbors are bacteria, it is expected that lateral gene transfer (LGT) from bacteria might have contributed to the evolutionary history of this organism. We performed a phylogenomic survey of putative lateral gene transfer events in M. stadtmanae, using a phylogenetic pipeline. Our analysis indicates that a substantial fraction of the proteins of M. stadtmanae are inferred to have been involved in inter-domain LGT. Laterally acquired genes have had a large contribution to surface functions, by providing novel glycosyltransferase functions. In addition, several ABC transporters seem to be of bacterial origin, including the molybdate transporter. Thus, bacterial genes contributed to the adaptation of M. stadtmanae to a host dependent lifestyle by allowing a larger variation in surface structures and increasing transport efficiency in the gut niche which is diverse and competitive